Osteological Re‐Assessment and Taxonomic Revision of "Tanius laiyangensis" (Ornithischia: Hadrosauroidea) from the Upper Cretaceous of Shandong, China. Issue 4 (5th March 2019) - Zhang, Yu‐Guang; Wang, Ke‐Bai; Chen, Shu‐Qing; Liu, Di; Xing, Hai
ABSTRACT: Tanius is the earliest named ornithischian genus from China. Since 1929, three species of this genus, namely T. sinensis (the type species), "T. chingkankouensis" and "T. laiyangensis", have been reported based on remains from the Wangshi Group of Shandong, China, and were previously recognized as hadrosaurines. Following the recent achievement of consensus on the phylogenetic placement of T. sinensis outside Hadrosauridae, the assignments of the "T. chingkankouensis" and "T. laiyangensis" material of hadrosaurid origin to the genus Tanius become problematic. Related taxonomic issues of "T. laiyangensis" therefore need re‐appraisals. Here, we provide an overall taxonomic revision of "T. laiyangensis" from the Jingangkou Formation of northeast Shandong, by means of approaches of comparative anatomy, phylogeny and geometric morphometrics. Our osteological comparisons confirm the hadrosaurine affinity of "T. laiyangensis", given the presence of a suite of characters largely typical of Hadrosaurinae in the single specimen (i.e., a nearly complete sacrum and a partial right ilium), including a dorsoventrally narrow central plate of the ilium with the depth/length ratio <0.80. In the proposed phylogenetic framework, "T. laiyangensis" is inferred to be a member of Kritosaurini within Hadrosaurinae, as the sister taxon to Secernosaurus koerneri . The relative warp analysis on the lateral outline of the supraacetabular process also reveals a close resemblance of shape between the two species. Based on these different lines of evidence and considering no identification of any diagnostic characters from the specimen, we argue that the "T. laiyangensis" material comes from an indeterminate kritosaurin hadrosaurine in Asia. Anat Rec, 303:790–800, 2020. © 2019 Wiley Periodicals, Inc.